Functional MRI study of gender effects in brain activations during verbal working memory task - Tüdös, Zbyněk; Hok, Pavel; Hluštík, Petr; Grambal, Aleš (Physiological research, 2018)
Neuroimaging methods have been used to study differences of brain function between males and females. Differences in working memory have been also investigated, but results of such studies are mixed with respect to behavioral data, reaction times and activated brain areas. We tried to analyze functional MRI data acquired during the working memory task and search for differences of brain activation between genders. 20 healthy right-handed volunteers (10 males and 10 females) participated in the study. All of them were university students or fresh graduates. Subjects underwent block designed verbal working memory task (Item Recognition Task) inside the MRI scanner. Standard single-subject pre-processing and group fMRI analyses were performed using the FEAT software from FSL library. In the behavioral data, there was no statistically significant difference in the number of correct responses during the task. The task activated similar bilateral regions of frontal, parietal, temporal and occipital lobes, basal ganglia, the brainstem and in the cerebellum, which corresponds to the previous verbal working memory neuroimaging research. In direct comparison, there was no statistically significant difference in brain activation between small samples of male and female young healthy volunteers.
Keywords: reakční čas; Young Adult; Male; Psychomotor Performance; Sex Characteristics; magnetická rezonanční tomografie; mladý dospělý; Brain; psychomotorický výkon; krátkodobá paměť; Reaction Time; mužské pohlaví; pohlavní dimorfismus; Verbal Behavior; lidé; ženské pohlaví; verbální chování; Humans; mozek; Magnetic Resonance Imaging; Female; Memory, Short-Term